Analisis Perubahan Garis Pantai Di Kecamatan Mawasangka Timur Kabupaten Buton Tengah - Moh. Nur Ihsan Manaf; Nurgiantoro Nurgiantoro; Sawaludin Sawaludin; Ahmad Hidayat (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Shoreline monitoring and its changes can be carried out with remote sensing technology using satellite imagery. The use of satellite imagery data to monitor shoreline changes has several advantages, namely being able to monitor a wide area coverage in a relatively short time. The research aims to: (1) Analyze the shoreline changes that occurred in East Mawasangka District 2009-2021; (2) Identify the factors that cause shoreline changes. The data used in this research are Landsat 7 and 8 imagery, analyzed using the DSAS (Digital Shoreline Analysis System) method. The results of this study are: (1) In 2009-2021 there are 4 areas that experienced shoreline changes. The abrasive area with the biggest change is in Area 2 with a change of 150.04 m and the smallest change is in Area 4 with a change of 0.03 m. While the accreted area occurs in Area 2 with a total change of 225.19 m, Area 4 with a change of 0.01 m: (2) Factors influencing changes in the coastline, both sediment buildup, influence of currents, and height wave.